Strengthening Weselpos Domestic Product Competitiveness Using Business Model - Hardiyanto, Hardiyanto; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
Financial service business of PT. Pos Indonesia has been showing the significant growth for contribution revenues. The contribution of financial service business to PT. Pos Indonesia revenues is up to 34% at 2011. Financial service business has potential to increase the revenue by its potential large market and its competitive advantage. The revitalization plan of PT. Pos Indonesia explained that financial service business will be increased on the transaction number and on product portfolio. Currently, not all financial service products of PT. Pos Indonesia have equitable growth. Weselpos domestic product is a product which has decreased the number of transactions from year to year. In formulating business strategies, the analysis of business environment is done either externally and internally to get SWOT (Strength, Weakness, Opportunity, and Threat) of the business. The root cause problem is PT. Pos Indonesia is insensitive about business environment change. The root cause problem of the business is addressed using TOWS Matrix strategic formulation and business model to strengthen the strategy with strategic positioning as a guideline. Differentiation in the process of delivering services to consumers is proposed as strategic positioning, which is from human-based become automatic based. The strategies are focused on increasing customer satisfaction and increase customer loyalty. The implementation of the strategy consist of: create new products portfolio auto-service based, develop the existing products through the development of transaction process, making customer relationship management, and create the right marketing program. The implementation is needed one year time period.Â Keywords: Weselpos Competitiveness, Business Model, Weselpos Product Development, Financial Services